In Vivo Competitions between Fibrobacter succinogenes, Ruminococcus flavefaciens, and Ruminoccus albus in a Gnotobiotic Sheep Model Revealed by Multi-Omic Analyses - Yeoman, Carl J. (mBio, 2021)
Fibrobacter succinogenes, Ruminococcus albus, and Ruminococcus flavefaciens are the three predominant cellulolytic bacterial species found in the rumen. In vitro studies have shown that these species compete for adherence to, and growth upon, cellulosic biomass. Yet their molecular interactions in vivo have not heretofore been examined. Gnotobiotically raised lambs harboring a 17-h-old immature microbiota devoid of culturable cellulolytic bacteria and methanogens were inoculated first with F. succinogenes S85 and Methanobrevibacter sp. strain 87.7, and 5 months later, the lambs were inoculated with R. albus 8 and R. flavefaciens FD-1. Longitudinal samples were collected and profiled for population dynamics, gene expression, fibrolytic enzyme activity, in sacco fibrolysis, and metabolite profiling. Quantitative PCR, metagenome and metatranscriptome data show that F. succinogenes establishes at high levels initially but is gradually outcompeted following the introduction of the ruminococci. This shift resulted in an increase in carboxymethyl cellulase (CMCase) and xylanase activities but not in greater fibrolysis, suggesting that F. succinogenes and ruminococci deploy different but equally effective means to degrade plant cell walls. Expression profiles showed that F. succinogenes relied upon outer membrane vesicles and a diverse repertoire of CAZymes, while R. albus and R. flavefaciens preferred type IV pili and either CBM37-harboring or cellulosomal carbohydrate-active enzymes (CAZymes), respectively. The changes in cellulolytics also affected the rumen metabolome, including an increase in acetate and butyrate at the expense of propionate. In conclusion, this study provides the first demonstration of in vivo competition between the three predominant cellulolytic bacteria and provides insight on the influence of these ecological interactions on rumen fibrolytic function and metabolomic response.